2022
DOI: 10.1111/jocd.14734
|View full text |Cite
|
Sign up to set email alerts
|

Application and mechanism of probiotics in skin care: A review

Abstract: Recently, the concept of micro-ecological skin care has gradually been into people's life, which means that people have entered a new era in skin care. Micro-ecological skin care mainly refers to the improvement of skin barrier function and cell combination, accelerating of skin renewal and improvement of skin health by supplementing probiotics or prebiotics. 1 Probiotics are defined as living microorganisms which, when administered in adequate amounts, give a healthy benefit on the host. 2 Reports on the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 72 publications
0
22
0
Order By: Relevance
“…Thus, probiotic bacterial therapy has been suggested as having great potential in the treatment and prevention of skin conditions. Due to this skin health-promoting effect, several strains of probiotics are used as supplements in immune-mediated skin diseases (6,61). Many experimental studies have shown that the probiotics influenced on epithelial cells and on immune cells in the intestine, resulting in a lowering of allergic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, probiotic bacterial therapy has been suggested as having great potential in the treatment and prevention of skin conditions. Due to this skin health-promoting effect, several strains of probiotics are used as supplements in immune-mediated skin diseases (6,61). Many experimental studies have shown that the probiotics influenced on epithelial cells and on immune cells in the intestine, resulting in a lowering of allergic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of anti-aging interventions on the population and environment of gut microbiota were discussed in this paper [287]. Probiotics were also considered as anti-aging effectors in skin issues and dermatology [288].…”
Section: Pharmacological and Nutraceutical Interventionsmentioning
confidence: 99%
“…It is possible to provide probiotics in anhydrous formulations. [7][8][9][10][11][12][13][14] that are typically oil-based formulations where the living probiotics are embedded within the oil and are thus protected against contact with water which is necessary for them to grow. [7][8][9][10][11][12][13][14] Some companies, like Lactbio A/S, that have developed probiotic formulations using strictly anhydrous oil-based formulations.…”
Section: Introductionmentioning
confidence: 99%